Impact of Al-doping on structural, electrical, and optical properties of sol-gel dip coated ZnO:Al thin films - S Tipawan Khlayboonme; Warawoot Thowladda (Materials Research Express, 2021)
Aluminum-doped ZnO (AZO) thin films were coated on glass substrates using the sol-gel dip-coating technique. We investigated the effect of Al-doping level on the surface morphology, crystal structure, atomic bonding, and optical and electrical properties of the AZO films. The Al-doping levels in the sol-gel solution were 0, 0.25, 0.50, 1.0, 1.5, and 3.0% with a Zn precursor concentration of 0.50 M. The results show that the grain boundary increased with the doping level, while the crystallite size decreased from 27.2 to 14.2 nm. The AZO films were subjected to tensile stress. The Al-doping levels ≤ of 1.5% encouraged the intensity of the (002) x-ray diffraction peak. The center of the (002) peak shifted from 34.46° to 34.51°, and that of the ${{{\rm{E}}}_{2}}^{{\rm{high}}}$ Raman mode shifted from 435.0 to 432.4 cm ^−1 . Doping with 1.5% Al resulted in a maximum electron concentration of 4.7 × 10 ^18 cm ^−3 with a minimum resistivity of 2.6 × 10 ^−1 Ω cm and a mobility of 5.14 cm ^2 /V.s. The Urbach energy increased from 88 to 120 meV with increasing doping level. For the AZO films doped with Al (≤1.5%), the analysis of the UV–vis spectra reveals that the position of the conduction band (CB) minimum of the films shifted from −0.16 to −0.21 eV and shifted outward from the valence band (VB). Further Al doping to 3.0% resulted in a VB shift toward CB. The optical band gap reached a maximum of 3.33 eV at 1.5% Al. The combination of tensile stress and electron density due to Al doping influences the shift in the optical band gap of the AZO films. The crystal structure, atomic bonding, and electronic band structure of ZnO films can be modified by Al doping.